2017
DOI: 10.5943/mycosphere/8/10/11
|View full text |Cite
|
Sign up to set email alerts
|

Can ITS sequence data identify fungal endophytes from cultures? A case study from Rhizophora apiculata

Abstract: Culture-based studies have recovered fungal endophytes from numerous plant hosts, while direct examination of sporulating cultures has enabled identification. However, many endophytes cannot be identified due to the fact that they only form mycelia sterilia in culture. Although next generation sequencing (NGS), as well as ITS sequence analyses have been used to identify endophytes, identification is still rudimentary. In this study, we isolated fungal endophytes from Rhizophora apiculata in Thailand and establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…So far, a number of fungi collected from mangroves are either saprobes (e.g Swe et al 2008a, b, Devadatha et al 2018, Li et al 2018) or endophytes (e.g Liu et al 2012, Doilom et al 2017). One early species documented from mangroves is that of Stevens (1920) who reported a species of Anthostomella that was found from a leaf spot in red mangroves ( Rhizophoramangle ) in Puerto Rico.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a number of fungi collected from mangroves are either saprobes (e.g Swe et al 2008a, b, Devadatha et al 2018, Li et al 2018) or endophytes (e.g Liu et al 2012, Doilom et al 2017). One early species documented from mangroves is that of Stevens (1920) who reported a species of Anthostomella that was found from a leaf spot in red mangroves ( Rhizophoramangle ) in Puerto Rico.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of PSF identified fungal species names based on morphology, highest nucleotide similarity in MegaBLAST searches of NCBI’s GenBank nucleotide database and/or phylogenetic analysis of ITS sequence data ( Nelofer et al, 2015 ; Wang et al, 2018 ; Zhang et al, 2018 , Supplementary Table S5 ). However, these are insufficient to determine the species names, especially within species complexes ( Samson et al, 2014 ; Doilom et al, 2017 ; Hyde et al, 2020a , b ). A comparison of sequence data from fungal strains with the ex-type cultures of named species must be considered to confirm the species name ( Dayarathne et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro Antagonistic Activity: Test Microorganisms: The two fractions of the fungus were used for in-vitro antagonistic activity against bacteria include Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis, Escherichia coli, Salmonella typhi, and fungi include Candida albicans, Aspergillus flavus, Aspergillus niger, and Aspergillus fumigatus by well diffusion method 2,6,12,28 .…”
Section: Bioassaysmentioning
confidence: 99%
“…from the different fungal genera that possess a wide variety of biological activities including antimycobacterial, antibacterial, antifungal, antioxidant and anticancer 2,7 . Optionally, these all fungi are isolated and purified from different medicinal plants as endophytic fungi due to their ethnobotany and pharmaceutical applications [7][8][9][10][11][12] . In 1866, De Barry introduced the term "endophyte" for those microbes that reside inside the healthy tissues of plants without causing any apparent diseases [13][14][15][16] .…”
mentioning
confidence: 99%